On the Mitigability of Uncertainty and the Choice between Predictive and Nonpredictive Strategy - Packard, Mark D.; Clark, Brent B. (Academy of Management Review, 2020)
Managers face a critical issue in deciding when to employ a predictive planning approach versus a more adaptive and flexible strategic approach. We suggest that determining which approach is ideal for a given context hangs on the extent to which uncertainty is, or might be, mitigable within that context. To date, however, the mitigability of uncertainty has not been adequately distilled. Here, we take on this issue, distinguishing mitigable ignorance of pertinent but knowable information (i.e., “epistemic uncertainty”) from immitigable indeterminacy (i.e., “aleatory uncertainty”). We review the current state of the debate on the existence of free will, because the acceptance or rejection of conscious agents as a true first cause has fundamental implications. A critical examination of the arguments for and against the free will hypothesis land us on the side of voluntarism, which implies immitigable indeterminacy (but not complete unpredictability) wherever conscious actors are involved. Accepting the existence of immitigable or aleatory uncertainty, then, we revisit the determination of strategic logics and produce important theoretical nuance and key boundary conditions in the normative choice between predictive and nonpredictive strategies.